Current state of play for HPV-positive oropharyngeal cancers. (November 2022) - Deutsch, Fiona; Regina Bullen, Izabel; Nguyen, Kevin; Tran, Ngoc-Ha; Elliott, Michael; Tran, Nham
Highlights: Carcinomas of the oropharynx have increased in incidence with a rise in HPV16 infections. Standard treatment for patients with oropharyngeal cancers does not differ based on HPV status. An adequate de-escalation strategy has yet to be identified. Abstracte: Clinically, HPV-positive oropharyngeal cancers (OPCs) have been shown to have a distinct prognosis, compared to HPV-negative tumours, particularly in survival rates and responses to treatment. These patients have better survival chances and improved prognosis, indicating that a more exhaustive knowledge of these distinctions would aid in the discovery of clinical approaches for both HPV-positive and negative tumours. Furthermore, there is increasing evidence that HPV-related oropharyngeal cancers constitute an epidemiological, molecular, and clinical distinct form as compared to non-HPV related ones therefore, the treatment of these specific subtype of oropharyngeal cancers should adopt a distinct clinical treatment pipeline. Our review will examine the current approaches for the diagnosis and treatment of OPC and discuss the relevance of de-escalation clinical trials in progress.